Stimulus-driven reorienting in the ventral frontoparietal attention network: the role of emotional content - Frank, David W.; Sabatinelli, Dean (Frontiers in Human Neuroscience, 2012)
Activity in the human temporoparietal junction and inferior frontal gyrus is hypothesized to underlie stimulus-driven, or “bottom-up” attention reorienting. Demanding tasks require focused attention, and as task difficulty increases, activity suppression in the ventral network correlates positively with task performance, an effect thought to reflect the gating of irrelevant cues. However, activation in these structures is elicited by a range of stimulus features and task demands that vary across multiple characteristics, complicating the interpretation of the functional role of this pathway. Consideration of several current studies suggests that, in addition to task difficulty, the motivational relevance or emotional intensity of distractor stimuli may supersede ongoing task priority, and evoke ventral network activation. Support for this possibility is offered from a review of recent reports, and the import of this perspective for models of attention reorienting are discussed.